Evaluation of Anti-Centromere Antibodies, Anti-SSA and Anti-SSB in Serum and Saliva of Patients with Systemic Sclerosis - Mohassad H Al-Mudhaffar; Taghreed F Zaidan (College of Dentistry/ University of Baghdad, 2018)
Background: Systemic sclerosis (SSc) is a chronic autoimmune illness, which is consider by three main features: Sclerotic changes in the skin and internal organs, Vasculopathy of small blood vessels, Particular autoantibodies (1). The most important autoantibodies appeared significantly in SSc patients are anti-topoisomerase I autoantibody (Scl-70), anti-centromere autoantibody (ACA), and anti-RNA polymerase III autoantibody (RNAP3) (2). Anti-centromere antibodies (ACA) are infrequent in rheumatic conditions and in healthy persons but occur commonly in limited systemic sclerosis (CREST syndrome), and rarely appeared in the diffuse form of systemic sclerosis (3). Anti-Ro/SSA and antiLa/SSB, antibodies directed against Ro/La ribonucleoprotein complexes, can serve as a diagnostic hallmark of autoimmune disease specially Sjogren's syndrome (4). Materials and methods: This study was carried out during the period from the middle of November 2015 until the end of November 2016 in Baghdad city. The sample of this study was divided into two groups : Forty systemic sclerosis patients: Those patients were treated at Rheumatology department in Baghdad teaching hospital in Baghdad city as well as Forty healthy control subjects, age matched with no signs and symptoms of any systemic diseases. Results: The serum anti-SSA in SSc patient was significant increased as well as the salivary anti-SSA in SSc patient was highly significantly increased than in the control subjects by using t-test. The present study found that there no statically difference in salivary ACA, anti-SSB and serum anti-SSB while serum ACA was significantly increased. Conclusions: autoantibodies play a role in pathogenesis of SSc patients represented by increased serum (ACA and anti-SSA) that it considered reliable indicator for SSc patients while unpredicted marker in saliva except anti-SSA. Anti-La/SSB is unreliable marker in both serum and saliva SSc patients. The presence of Anti-Ro/SSA antibodies in serum and saliva of SSc patient has been predictive marker for SSc overlapped Sjogren's syndrome.